Mutual Relationship : Membangun Komunikasi Efektif Dengan Masyarakat - Muhammad Abrori (Aafiyah: Jurnal Multidisiplin Ilmu, 2023)
This study aims to analyze and understand building effective communication with the community to create a reciprocal relationship between the community and the institution MA Nurul Wahid Besuk, Probolinggo. This research uses a qualitative approach type of case study. The results showed that MA Nurul Wahid builds effective communication with the community through five components, namely: Commite As Liaison, which is an institution in collaboration with the madrasah committee to become a liaison to the community; Mapping Calss Group, which is a medium for interaction between teacher council guardians and parents; Social Service, namely to build the image of the institution, trust and good relations with the community; Home Visite, namely social activities carried out by institutions to improve effective communication with the community. By making a direct visit to the parent's home; Social Media, is media used by institutions to facilitate dissemination of information to the public. This research has implications for the importance of institutions building effective communication with the community to create reciprocal relationships, thus impacting public trust and public loyalty.